Utility of mean platelet volume in differentiating intrahepatic cholangiocarcinoma from hepatocellular carcinoma - Xin Zhang; Wen-Juan Huang; Meng-Lin Zhang; Wen Wang; Ye Niu; Rui-tao Wang; Zeng-yao Liu (BMC Gastroenterology, 2022)
Abstract Background Intrahepatic cholangiocarcinoma (ICC) and hepatocellular carcinoma (HCC) are the most prevalent histologic types of primary liver cancer. HCC and ICC differ in treatment and prognosis, warranting an effective differential diagnosis between them. This study aimed to explore the clinical value of mean platelet volume (MPV) to discriminate between HCC and ICC. Material/methods We performed a retrospective analysis of ICC and HCC patients who were from the Harbin Medical University Cancer Hospital, China. Logistic regression analysis was used to identify the independent factors for the differentiation of HCC and ICC. A receiver operating characteristic curve was built to evaluate the diagnostic performance of the potential model. An independent validation study was performed to validate the diagnostic ability. Results ICC patients were detected in 146 out of 348 patients in the primary cohort. MPV levels were decreased in ICC patients compared with those in HCC patients. Logistic regression analysis revealed that MPV was an independent factor in distinguishing HCC from ICC. A combination of sex, hepatitis B surface antigen, MPV, alpha-fetoprotein, and carbohydrate antigen 19–9 demonstrated a good capability to differentiate HCC from ICC. Similar results were achieved in the validation cohort. Conclusions MPV may be a new marker to help distinguish ICC from HCC. Further validation studies are required.